Rehabilitasi Tuna Sosial di Unit Pelaksanaan Teknis Dinas (UPTD) Rumoh Seujahtera Beujroh Meukarya Ladong Kabupaten Aceh Besar - Fadli Fadli (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2023)
Socially disabled is someone who, due to certain factors or not, is less able to carry out a decent life in accordance with the norms of social, religious or legal life. In this research, the Socially Disabled Persons referred to in the category of one type of problem, namely homeless people and beggars, are those who are registered with People with Social Welfare Problems (PMKS), of which there are still many problems in Aceh Province, one of which is (UPTD) Rumoh Seujahtra Beujroh Meukarya is a form of concern in the Social Disability Services Program, which is a Regional Government Program to reduce the number of homeless, homeless, beggar PMKS. This research aims to determine the Rehabilitation Process for Socially Impaired Persons at the Rumoh Seujahtra Beujroh Meukarya Ladong Technical Implementation Unit (UPTD). The method used in this research is the Qualitative Descriptive Approach Method. The collection techniques used in this research are observation, interviews and documentation. The subjects of this research were 7 informants consisting of 4 UPTD employees and 3 clients. The results of interviews and observations carried out showed that UPTD Rumoh Seujahtera Beujroh Meukarya in Ladong Aceh Besar Regency had a rehabilitation process, various forms of rehabilitation guidance were provided and there were changes to clients after rehabilitation services were provided to them.